2017
DOI: 10.3390/su9071188
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Power Load Forecasting Based on Sperm Whale Algorithm and Wavelet Least Square Support Vector Machine with DWT-IR for Feature Selection

Abstract: Short-term power load forecasting is an important basis for the operation of integrated energy system, and the accuracy of load forecasting directly affects the economy of system operation. To improve the forecasting accuracy, this paper proposes a load forecasting system based on wavelet least square support vector machine and sperm whale algorithm. Firstly, the methods of discrete wavelet transform and inconsistency rate model (DWT-IR) are used to select the optimal features, which aims to reduce the redunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 29 publications
0
32
0
1
Order By: Relevance
“…Ma et al [30] employed the IR model to select the input features of the short-term load forecasting model, whose simulation result demonstrated that the IR model gave the input vector of the strong pertinence of the prediction model, and reduced the redundancy of the input information, thus improving the accuracy of load forecasting. Liu et al [31] also selected the optimal features for forecasting power load by adopting the IR model so as to reduce the redundancy of input vectors, and the IR model obtained an ideal feature selection effect. Using the IR model for feature selection can not only eliminate redundancy features by utilizing the inconsistency of the data set, but also take the correlative characteristics among the features into consideration, which does not ignore the relationship among features so that all the statistical information can be perfectly expressed by the selected optimal feature.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [30] employed the IR model to select the input features of the short-term load forecasting model, whose simulation result demonstrated that the IR model gave the input vector of the strong pertinence of the prediction model, and reduced the redundancy of the input information, thus improving the accuracy of load forecasting. Liu et al [31] also selected the optimal features for forecasting power load by adopting the IR model so as to reduce the redundancy of input vectors, and the IR model obtained an ideal feature selection effect. Using the IR model for feature selection can not only eliminate redundancy features by utilizing the inconsistency of the data set, but also take the correlative characteristics among the features into consideration, which does not ignore the relationship among features so that all the statistical information can be perfectly expressed by the selected optimal feature.…”
Section: Introductionmentioning
confidence: 99%
“…Transforming this quadratic programming problem to its corresponding dual optimization problem and introducing the kernel function in order to achieve non-linearity yields an optimal regression function as [25] …”
Section: Least Squares Support Vector Machinementioning
confidence: 99%
“…As this procedure has a significant impact on the performance of the SSFS-GMDH model, it is crucial to choose a proper basic classification model. Therefor three basic and effective classification models include the Support Vector Machines [7], Bayesian Networks [53], and Decision Trees [54,55] are employed in this paper. Each experiment is conducted 30 times via MATLAB2016b.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Electricity load forecasting can be classified into long-term [3], medium-term [4], short-term [5][6][7] and ultra-short term [8], and the cut-off points for these four categories are three years, two weeks, and one day, respectively [9]. The short-term load forecasting (STLF), which is applied to horizons no more than one day ahead, can result in significant environmental and economic benefits for energy systems.…”
Section: Introductionmentioning
confidence: 99%